Training the Workforce to Conduct Embedded Pragmatic Clinical Trials to Improve Care for People Living with Dementia and Their Caregivers. (26th June 2020) - Callahan, Christopher M.; Torke, Alexia M.; Alder, Catherine A.; Broughton, Jessica A.; Mitchell, Susan L.
Abstract : The National Institute on Aging IM bedded P ragmatic A lzheimer's Disease and Alzheimer's Disease–Related Dementias C linical T rials (IMPACT) Collaboratory serves as a national resource for the conduct of embedded pragmatic clinical trials to improve the care of people living with dementia (PLWD) in partnership with the healthcare systems that serve them. Inherent in this objective is the need to train and support a cadre of investigators prepared to conduct this work now and in the future. The Training Core of the IMPACT Collaboratory supports the training of investigators to become experts in this field through three objectives: (1) curricula development and dissemination; (2) network generation and navigation; and (3) a career development award program. The innovative approach of the Training Core will require developing content and providing training experiences that recognize the unique challenges of research at the intersection of health systems, pragmatic trials, and PLWD and their caregivers. Ultimately, we seek to build the nation's capacity to conduct research that bridges the gaps between efficacy studies to effectiveness research to implementation science. Although foundational resources in the methods of each of these areas are already available, few actually focus on pragmatic trials embedded within healthcare systems that focus on PLWD. To bring new interventions for PLWD from efficacy to widespread implementation, researchers must build diffusability, adaptability, heterogeneity, and scalability into the design of the intervention. In achieving these objectives, the Training Core will utilize the network of investigators, institutions, and stakeholders represented in the IMPACT Collaboratory. J Am Geriatr Soc 68:S21–S27, 2020 .